Advanced Techniques for Improving Model Robustness in Adversarial Machine Learning (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This work investigates advanced methods for improving the resilience of machine learning models against adversarial attacks. Ensuring that these models can withstand deliberately crafted inputs—called adversarial examples—has become critical as machine learning expands into high-stakes fields such as computer vision, cybersecurity, and healthcare. The study examines several types of adversarial attacks, including black-box attacks, where the attacker has no direct knowledge of the model, and white-box attacks, where the attacker has complete access to the model. Popular defense strategies, such as the Fast Gradient Sign Method (FGSM), Iterative FGSM (I-FGSM), and the Carlini and Wagner (C&W) attack, are also discussed. The work emphasizes how adversarial learning contributes to creating more resilient models by addressing both theoretical foundations and practical applications. This thorough investigation highlights the strengths and weaknesses of current approaches, as well as the ongoing need for advancements to protect model integrity against evolving threats.